ORGANIZATIONAL AND ECONOMIC MECHANISMS OF TRANSPORT SYSTEM DEVELOPMENT BASED ON LOGISTICS - IRTYSHCHEVA, INNA; ISHCHENKO, OLENA; BARABANOVA , JULIA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
It is determined that the existence of a developed transport and logistics infrastructure is one of the defining dominants of the effective functioning of the transport and logistics system at the regional, national and international level, provides effective supply, marketing, production and social communications between the subjects of economic activity. It is proved that the main directions of state policy implementation in the field of transport and logistics are: directions of innovative development of transport and logistics technologies on energy-saving and environmentally safe principles; construction of efficient economic systems in accordance with the principles of logistics and marketing; development of strategic planning; improvement of regulatory policy. Institutional, organizational and economic mechanisms for ensuring the effective development of national transport and logistics systems have been researched and systematized, among which the following have been identified as priorities: the development of public-private partnerships and decentralization reform, which will solve the problems of financing infrastructure development, the formation of multi-branch integration structures (transport-logistics clusters, transport hubs and logistics-outsourcing platforms), which will improve the quality of transport and logistics services, intensification of the integration processes of the transport and logistics system in the international transport of the network, which will increase the competitiveness of the national economy, increase in productivity of transit potential and attraction of foreign investments in the development of the industry.